Studying the Frequency of Autoimmune Thyroid Diseases in Duhok Province - Hasan, Rozheen I.; Raziq, Amir H. (Science Journal of University of Zakho, 2019)
Thyroid disorders are one of the most frequent disorders affecting endocrine system. The present study aimed to identify the frequency of thyroid disorder in our locality at Duhok city. To do so, a total of one hundred patients and one hundred apparently healthy control individuals were enrolled in this study. Samples of venous blood (5 ml) were withdrawn from patients and control subjects and analysed. Clinical assessment was performed by a specialist and each patient provided with a document supporting preliminary clinical diagnosis. Measurements of serum TSH, T3, T4, and anti-thyroperoxidase antibodies (anti-TPO antibodies) serum levels were performed. All assays were conducted at Duhok central health laboratory. Out of the one hundred patients and the one hundred control groups, forty-two and thirty candidates were randomly selected, respectively. The mean TSH serum levels of 25.87 (uIU/ml) for the patients significantly differ from that of the control group 3.55 (uIU/ml) (p<0.001). However, T3 and T4 serum levels indicated no significant difference between the two categories. Moreover, there was statisticaly significant difference (p< 0.0001) between the patients and control groups when their mean serum anti-TPO concentrations were compared. In conclusion, considerable number of subjects appeared to be candidates for deranged thyroid functions and is susceptible to autoimmune thyroid disorder.